Coupled-oscillator-humanizer revealed possible ensemble players’ ability to discriminate cross-correlation structures in auditory sequences of paired drum tapping - Masahiro Okano; Sotaro Kondoh; Wataru Kurebayashi; Ryosuke O. Tachibana (PLoS ONE, 2025)
Natural fluctuations in the timing sequence are essential for a dynamic and expressive rendition of music. Various studies have demonstrated the statistical structure of such timing fluctuations in solo music performances and listeners’ ability to perceive them. However, the listening ability of timing structures in ensemble performances involving multiple players remains unclear despite its importance in understanding actual music skills. Here, we assessed listeners’ ability to distinguish the statistics of timing variations that resembled mutual adaptations between a pair of tapping players as a simplified example of ensemble performance. We created sound stimuli in which the drum-tapping timing sequences fluctuated either cooperatively among the pair or randomly using a generative model for synchronized pair tapping. Listing tests to discriminate between these stimuli, and a questionnaire on music experience and sophistication were conducted as a web-based experiment. Consequently, a trend was observed where participants with ensemble experience could discriminate between stimuli, whereas participants without ensemble experience could not. This discrimination ability did not correlate with the musical sophistication index. These results suggest that listeners with a certain music experience, particularly those involved in ensemble performances, can perceive the individuality of each player and the coordination between them based on the timing sequence structure.